Unionized Construction Workers are More Productive - Allen, Steven G. (Quarterly Journal of Economics, 1984)
This paper presents evidence on the effect of unionism on productivity in construction. The linkages are distinct from those studied previously in industrial settings. Apprenticeship training and hiring halls probably raise union productivity, while jurisdictional disputes and restrictive work rules lower it. Using Brown and Medoff's methodology, union productivity, measured by value added per employee, is 44 to 52 percent higher than nonunion. The estimate declines to 17 to 22 percent when estimates of interarea construction price differences are used to deflate value added. Occupational mix differences and, possibly, apprenticeship training account for 15 to 27 percent of this difference.